PERMASALAHAN DAN SOLUSI PADA PEMBELAJARAN BAHASA INDONESIA DI TINGKAT SEKOLAH DASAR - Ratnawati, Fitria (CULTURAL EDUCATION JOURNAL OF LITERATURE AND CULTURE, 2023)
Research problems in learning Indonesian in low grade SD Negeri 2 Percontohan Blangkejeren needs to be done because there are many problems faced by teachers at this time. The research aims to find out the problems in learning Indonesian in low class. This type of research is descriptive qualitative. Participants in this study were 1 class I teacher, 1 class II teacher, and 1 class III teacher. Data collection techniques using observation, interviews, and documentation. Data analysis in this study uses source triangulation and technique triangulation. The results of the study showed that the problems faced by the teacher were that low grade students still had difficulty listening, speaking, reading and writing. The teacher has a strategy in learning Indonesian on language skills (listening, speaking, reading and writing). The teacher takes a direct approach to students who have difficulty in listening, speaking, reading and writing, by guiding if there are students who have difficulty reading or writing until the students are fluent. The teacher also accustoms students to read wherever, for example in the canteen on snack packs, in public places, in parking lots, on school grounds. Students who have difficulty writing will be guided by copying the writing on the board, copying the writing in the book. Students who have difficulty listening or pay less attention will immediately be called by the teacher to come forward. Students who have difficulty speaking Indonesian properly and correctly will be accustomed to communicating in Indonesian.